Potret Pergundikan di Hindia Belanda - Mirnawati, Mira; Sarimanah, Eri; Dewi, Figiati Indra; Efendi, Roy (Ideas Publishing, 2026)
This study aims to describe the practice of concubinage during the Dutch East Indies as represented in Pramoedya Ananta Toer's novel Bumi Manusia. The study uses a qualitative approach with a descriptive-analytical method. The research data consists of primary data in the form of the novel text Bumi Manusia and secondary data obtained from books, scientific articles, and relevant historical sources. The data collection technique was carried out through literature study, while data analysis was carried out by carefully reading, classifying, and interpreting the data according to the focus of the study. This study focuses on three main issues: the practice of concubinage, marriage without legal status, and the sociocultural impact of this practice. The results show that the practice of concubinage in Bumi Manusia involves an unequal power relationship between European men and indigenous women. Concubinage gave rise to a form of marriage without legal recognition, while also giving rise to sociocultural impacts in the form of changes in the behavior of concubines, social stigma from society, and issues of the legal status of children resulting from concubinage